CEC model evaluation group: an account of the activities of the Heavy Gas Dispersion Expert Group. (4th August 2014) - Mercer, A.; Bartholome, C.; Carissimo, B.; Duijm, N.J.; Giesbrecht, H.
The heavy gas dispersion expert group is one of the three groups so far set up by the CEC Model Evaluation Group. This paper describes the activities of the group. The main results of these activities are: (i) a tested heavy gas dispersion model evaluation protocol, (ii) a list and classification of available models and (iii) a list and classification of relevant datasets.